Effect of titanium dioxide nanoparticle ( TiO 2 ‐ NP ) exposure in a novel Amur sturgeon Acipenser schrenckii hepatocyte cell line - Zhou Zhou; Ting Liu; Tianxun Luo; Zhenxing Zhao; Junquan Zhu (Journal of Fish Biology, 2024)
In vitro cell culture is crucial for predicting the toxicity of titanium dioxide nanoparticle (TiO 2 ‐NP). However, assessing the toxicity of TiO 2 ‐NPs in sturgeon remains difficult given the lack of sufficient cell lines. We established and characterized the first hepatocyte cell line from Acipenser schrenckii liver tissue (ASL). This ASL cell line proliferated well in Dulbecco's modified Eagle's medium at 25°C and 10% fetal bovine serum. ASL cells with a chromosome number of 244 were successfully transfected with the pEGFP‐N3 plasmid. The ASL cell line's origin was verified as A. schrenckii through mitochondrial cytochrome C oxidase I and mitochondrial 16S ribosomal RNA (rRNA) sequencing. Using the ASL cell line as an in vitro model, we found that TiO 2 ‐NP exposure decreased the viability and promoted the damage of ASL cells (96‐h LC 50 = 331.8 μg mL −1 ). Increased reactive oxygen species and malondialdehyde levels in ASL cells suggested oxidative stress under TiO 2 ‐NP exposure. We also observed dysregulation of aspartate aminotransferase and alanine aminotransferase levels. By detecting calcium ions and mitochondrial membrane potential indicators, we found that the apoptotic pathway induced by endoplasmic reticulum stress played a major role at low concentrations of TiO 2 ‐NP‐induced stress. Both mitochondria‐mediated and endoplasmic reticulum stress promoted apoptosis under increasing TiO 2 ‐NP concentrations. In conclusion, the ASL cell line established in this study is a useful in vitro model for toxicological studies of TiO 2 ‐NP exposure in fish.